Analisis Komunikasi Visual Mural Karya Studio Imaginer House Di Café Wow Ponorogo - Jeremiah, Sean Elbert (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2024)
In this digital era, visual communication has become an inseparable element in conveying messages and artistic expression. One of the forms of expression can be found in mural art. In Indonesia, mural art has developed very rapidly, so many mural studios have sprung up to offer mural-making services, one of which is Imaginer House mural studio in Malang City. The mural in Wow Ponorogo café by Imaginer House Studio is not only a visual decoration, but also creates a unique atmosphere and illustrates the values and concepts that want to be conveyed, so a research is conducted to analyze the visual communication. The method used is qualitative method with descriptive research. To find out the meaning using Barthes' simeotics theory. This analysis is done in order to know about visual communication such as themes, meanings, and design principles that exist in the Wow Ponorogo café mural.